IDAROH TAQYIM AL- BAROMIJ AL-‘ARABIYYAH (FI TAKWIN AL-BI’AH AL-LUGHAWIYYAH) FI MASKAN MANHALUN AN-NABIGHIN - Rahmadani Lubis; Romy Aria Pranata; Zakiyah Arifa (El-Tsaqafah : Jurnal Jurusan PBA, 2021)
This study aims to identify and explain about the Arabic languageprogram in Manhalun Nabighin and evaluation management in theArabic language program in Manhalun Nabigin. As for the backgroundof this research is the fact that Manhalun Nabighin is a course institutionthat organizes Arabic language learning for all groups, especially studentsof all majors, which certainly require special handling. This research usesdescriptive qualitative research. The research method used to collect datathrough interview techniques, observation and documentation. After thedata is collected, data analysis is carried out by: 1) data reduction, 2) datapresentation, 3) drawing conclusions / verification. The results showed thatthe Arabic language program was included in the nabighin manhalun, namelynahwu point zero with the syawir method, the implementation of programevaluation at Maskan Manhalun Nabighin used the discrevancy model or thegap model, the Goal-Oriented Evaluation Model and the Decision OrientedEvaluation Model. This evaluation is carried out for continuous improvementwhich will be carried out every month to improve the program in creating amore conducive Arabic language environment.